A rare case report of congenital high airway obstruction syndrome presenting in a 23 weeks foetus - Kanchana, Madurai Padmanabhan; Sellamuthu, Muthu Prabha; Mahendran, Revathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Congenital High Airway Obstruction Syndrome or CHAOS is a blockage of the foetus’s trachea or larynx due to many factors including narrowing of the airway, a web-like membrane or even tracheal atresia. In the uterus, the foetal lungs constantly produce fluid and as a result of this airway blockage in the trachea, the lung fluid cannot escape out of the foetal mouth. Because of this the foetus’s lungs become distended with fluid and over distended lungs can put pressure on the heart and affect the heart’s ability to function. If the heart cannot function effectively hydrops or congestive heart failure can occur. We present a rare case of CHAOS diagnosed prenatally at about 23 weeks by USG in our hospital.